Aflatoxins and ochratoxin A in export quality raisins collected from different areas of Pakistan. Issue 1 (2nd January 2016) - Asghar, Muhammad Asif; Ahmed, Aftab; Iqbal, Javed
ABSTRACT: During 2012–2014, 170 samples of export quality raisins were collected from different vendors in Pakistan. The collected samples were analysed for the presence of aflatoxins (AFs) and Ochratoxin A (OTA) contamination using high-performance liquid chromatography technique. The limit of detection and limit of quantification of AFs/OTA were 0.12/0.10 and 0.36/0.30 µg kg −1, respectively. Only 5% of the samples were contaminated with AFs, ranging 0.15–2.58 µg kg −1 with a mean of 0.05 ± 0.26 µg kg −1 . None of the raisin samples exhibited AFs contamination above the maximum limit (ML = 4 µg kg −1 ) as set by the European Union (EU). About 72% of the samples were contaminated with OTA, ranging 0.14–12.75 µg kg −1 with a mean of 2.10 ± 1.9 µg kg −1 . However, in 95.3% of the tested samples, OTA level was lower than the ML of 10 µg kg −1 as regulated by the EU. Apparently, a strict and continuous monitoring plan, including regulatory limits, improves food safety and quality for all types of commodities.